2021
DOI: 10.1093/jn/nxab075
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Prenatal, Perinatal, and Early Childhood Vitamin D Status and Risk of Dental Caries at 6 Years

Abstract: Background Previous studies have suggested that insufficient concentrations of vitamin D are associated with dental caries in primary teeth, but evidence remains inconclusive. Objectives We assessed the longitudinal associations between prenatal, perinatal, and early childhood serum 25-hydroxyvitamin D concentrations [25(OH)D] and the risk of dental caries in 6-year-old children. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 40 publications
1
28
0
2
Order By: Relevance
“…Our finding adds to the growing literature pointing to an association between low 25(OH)D and caries in children [4,10,12,21,22]. While most of these studies are crosssectional in design, there is emerging evidence from prospective studies that also indicate an inverse relationship [10,22,23]. A recent vitamin D supplementation study involving a cohort of Canadian children from Winnipeg recently reported a significant inverse relationship between cord 25(OH)D levels and dt (i.e., number of decayed primary teeth) scores in infants [22].…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Our finding adds to the growing literature pointing to an association between low 25(OH)D and caries in children [4,10,12,21,22]. While most of these studies are crosssectional in design, there is emerging evidence from prospective studies that also indicate an inverse relationship [10,22,23]. A recent vitamin D supplementation study involving a cohort of Canadian children from Winnipeg recently reported a significant inverse relationship between cord 25(OH)D levels and dt (i.e., number of decayed primary teeth) scores in infants [22].…”
Section: Discussionsupporting
confidence: 55%
“…A recent Chinese study reported that children with optimal 25(OH)D levels had a significantly lower prevalence of ECC [21], while a small study from Iraq reported significantly higher 25(OH)D levels among caries-free preschool children [26]. However, another study revealed a statistically weak relationship between 25(OH)D status in early childhood and caries in primary teeth in children who were 6 years old [23]. A recent Spanish birth cohort study reported that low prenatal and childhood vitamin D levels were associated with caries in the permanent teeth of children [27].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there have been three dental health studies published (one only as a conference proceeding) with access to prenatal and early life 25OHD data through previous longitudinal studies [ 17 , 27 , 28 ]. Suarez-Calleja et al obtained 25OHD from the INMA-Asturias birth cohort to assess dental caries prevalence in 188 children aged between 6 and 10 [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study found that 25OHD insufficiency (<50 nmol/L) in the first trimester of pregnancy and in children at 8 years-of-age were risk factors for dental caries, with odds ratios of 2.51 and 3.45, respectively [ 27 ]. Navarro et al (2021) [ 28 ] utilised 25OHD data from a cohort study in The Netherlands ( n = 5257), with maternal serum levels available from the second trimester and from participants at birth and at age 6. Participants with severe prenatal and early childhood serum 25OHD deficiencies (<25 nmol) were more likely to experience dental caries than those with mild or no deficiency, but this association was weak [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Calcium and 1,25-dihydroxy vitamin D homeostasis are essential for the formation and maintenance of teeth (33). In fact, low levels of calcium were already associated with dental caries in children (26,27,34,35), as well as low levels of 1,25-dihydroxy vitamin D (36). Low calcium levels are detected by extracellular calcium receptors in the parathyroid glands, which increase PTH gene transcription and secretion.…”
Section: Discussionmentioning
confidence: 99%